Influence Service Quality and Tuition Fee on Student Satisfaction During The Handling of Covid-19 Outbreak - Dewi Murtiningsih; Widi Wahyudi (Research Synergy Foundation, 2021)
The purpose of the research is to find out service quality and tuition fees on student satisfaction (partially or simultaneously). The type of this research is explanatory research. The population used in research is all 5,594 students of Budi Luhur University. The sampling technique used is proportional sampling. The number of samples used in this research is 110. SPSS is used as an analysis tool. The result of this research shows that service quality influences student satisfaction, tuition fee influences student satisfaction, and service quality and tuition fee simultaneously influence student satisfaction.